TIAA 2021 - Rosenthal, Jean; Sudhir, K.; Elias, Jaan (London : Yale School of Management, 2021)
TIAA had undergone an amazing turnaround. This nonprofit was established in 1918 to offer top-notch financial services to those who worked for other nonprofits, particularly higher education - a market underserved by other financial service providers. The company had a virtual stranglehold on these retirement accounts by the second half of the twentieth century, and marketing was an afterthought. However, well-known businesses like Fidelity and Vanguard started partnering with university institutions and providing services to their employees around the beginning of the new millennium.The management of TIAA believed that the company needed to modernise its strategy and concentrate on its clientele in order to survive. The company's product selection had always been limited, reflecting a somewhat paternalistic belief that its few items were all that customers needed to safeguard their financial future. As a result of internal product innovation and acquisitions of other financial companies, TIAA increased the scope of its products in response to the challenge posed by the competition.Additionally, TIAA started a campaign to raise its profile. For a very long time, TIAA stayed out of the public eye because it thought that its lengthy history of wise investing was enough of a calling card for the company. However, TIAA began producing advertising campaigns in 2006 that highlighted the company's offerings and commitments for the first time. Customers become more aware of TIAA.Through these initiatives, TIAA was able to keep its presence in the nonprofit sector and even broaden the range of organisations it provided services to. However, the company understood that in order to grow, it needed to keep its message to its clientele new. TIAA still was pretty much unknown in comparison towards its rivals, but there was potential to expand the company's reach.In 2021, TIAA sought to draw in and assist all prospective clients at the charitable organisations it supported. Non
Description based on XML content.
Keywords: elektronické knihy; electronic books; Teachers Insurance and Annuity Association; Bank management